Identifikasi Perilaku Masyarakat terhadap Saluran Udara Tegangan Ekstra Tinggi (SUTET) 500 kV Tanjungjati – Purwodadi - Istiarti, Tinuk (Jurnal Promosi Kesehatan Indonesia, 2011)
SUTET built to add aground electrical system, but still a lot of people who have negative perception of its existence and many rejection behaviors committed by people who reside in EHV transmission lines and surrounding areas. The research method used is explorative with quantitative and qualitative approaches. Samples were taken by random sampling study of 60 respondents and 3 District: Pati, Kudus, Jepara. The qualitative data collected through in-depth interviews and focus group discussions on community leaders of each 12 respondents in each district. The results showed that public attitudes about SUTET and the impact of population health and the environment is relatively still less agree, although when viewed from the knowledge and practice against SUTET pretty good. As for the problems in the implementation of replacement systems SUTET and land-use and compensation that are not clearly lead to negative perceptions and social jealousy in the community.